Diagnostic and prognostic values of conjunctival and oral biopsies analyzed by direct immunofluorescence in patients with mucous membrane pemphigoid - Jakubowska, Beata; Pietrzyk, Ewelina; Maciejewicz, Piotr; Kowalewski, Cezary; Wozniak, Katarzyna (Frontiers in Medicine, 2023)
Introduction Mucous membrane pemphigoid (MMP) is diagnosed on the basis of a characteristic clinical picture (a predilection for mucosal involvement and scarring in the affected tissues) and a positive direct immunofluorescence (DIF) result. Methods In this study, we compare the diagnostic and prognostic values of conjunctival and oral biopsies analyzed by DIF in patients with MMP. Sixteen patients with MMP and mucosal involvement as a predominant symptom were classified into three groups based on the clinical picture. Oral and conjunctival DIF were performed on all patients. Results Our study showed that patients with simultaneous oral and conjunctival involvement had a positive oral DIF in 83% and a positive ocular DIF in 100% of the examined cases, respectively. Patients with isolated ocular MMP had a positive oral DIF in 50% and a positive ocular DIF in 66% of the examined cases, respectively. Patients with only oral involvement with MMP had a positive oral DIF in 100% and a positive ocular DIF in 50% of the examined cases, respectively. Discussion Oral biopsy should be performed first and is usually sufficient for the diagnosis, even in patients with exclusively ocular MMP, whereas in patients without clinical ocular involvement, ocular DIF is positive in half of the cases and may be a predictive factor for ocular lesions in the future.